Rancang Bangun Website Responsif untuk Marketplace Online Berbasis Koperasi - Wahyu Ridhoni (Phasti: Jurnal Teknik Informatika Politeknik Hasnur, 2018)
Online marketplace has grown rapidly since last seven years, becoming a business with value of hundreds of billions rupiah [1]. This business model is generally established with ,Business Entity in the form of PT (Limited Liability Company), but actually in Indonesia there is another form of business entity which is also recognized by the government, Cooperative.Setiawan [2] explained that cooperative business processes need to be supported digitally. OnlineMarketplace as a new trend becomes one of the answers for cooperatives. The seller's membership in the marketplace can be unified with the membership of the cooperative, so that the cooperative business entity becomes more competitive. In the long run through this research, it is expected to grow a national-scale cooperative capable of accommodating this business model.This study aims at designing and building responsive web for online marketplace based on cooperative, where it can accommodate various screen size of digital devices. The website is built using waterfall method. Starting from the stage of analysis, design, implementation, and testing [3].The result of this research is a cooperative based online marketplace can be designed and built into a responsive website by combining features of product galleries and transactions with membership and co-operative savings. Kata Kunci— website responsif, marketplace, koperasi